2013
DOI: 10.5539/jedp.v3n2p153
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in 5- to 8-Year Olds: Developmental Changes and Relationship to Academic Achievement

Abstract: Pronounced improvements in executive functions (EF) during preschool years have been documented in cross-sectional studies. However, longitudinal evidence on EF development during the transition to school and predictive associations between early EF and later school achievement are still scarce. This study examined developmental changes in EF across three time-points, the predictive value of EF for mathematical, reading and spelling skills and explored children's specific academic attainment as a function of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 56 publications
5
34
0
1
Order By: Relevance
“…At the same time, not all of the reviewed studies found task improvement with age in samples of children from developing countries or severely disadvantaged communities, these generally being reported for children from developed countries (Roethlisberger, Neuenschwander, Cimeli, & Roebers, ). Results reported by Legare et al () showed that linear improvements with age on a three‐dimensional DCCS task were only apparent in the U.S. American sample but not in the sample of children from economically disadvantaged communities in South Africa.…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, not all of the reviewed studies found task improvement with age in samples of children from developing countries or severely disadvantaged communities, these generally being reported for children from developed countries (Roethlisberger, Neuenschwander, Cimeli, & Roebers, ). Results reported by Legare et al () showed that linear improvements with age on a three‐dimensional DCCS task were only apparent in the U.S. American sample but not in the sample of children from economically disadvantaged communities in South Africa.…”
Section: Discussionmentioning
confidence: 97%
“…Given the unitary structure of executive functions during childhood, the three measures of executive functioning were combined into a composite score based on the mean of the z-standardized scores for the three subtests (see Röthlisberger, Neuenschwander, Cimeli, & Roebers, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…EF abilities are responsible for directing, adapting, switching, and monitoring tasks (Miyake et al 2000), and contribute to writing and spelling productions (Altemeier et al, 2006;Åsberg Johnels, Kopp, & Gillberg, 2014;Berninger et al, 2009). Most studies examining EF components and their links with spelling analyzed written language skills in a general manner (Hooper et al, 2010;Roebers & Jäger, 2014;Röthlisberger et al, 2013), and showed that inhibition and cognitive flexibility explained variance in reading and writing performance (Altemeier et al, 2008) without describing each component's role. Nonetheless, few studies established links between each component and spelling acquisition.…”
Section: Links Between Executive Functions and Spellingmentioning
confidence: 99%